Methotrexate and Malignancy in Rheumatoid Arthritis: Evidence, Risks, and Clinical Considerations - Shigeru Iwata; Masahiro Tada; Ryuji Koike; Yuji Yamanishi; Mie Fusama; Haruka Tsuchiya; Kunihiro Yamaoka; Hideto Kameda (Modern Rheumatology, 2026)
Abstract In this review, we summarized the current evidence on the risks of incident malignancy and cancer recurrence in patients with rheumatoid arthritis (RA) treated with methotrexate (MTX). Before considering the effect of MTX, it is important to recognize the malignancy risk associated with RA itself. The overall risk of malignancy in patients with RA modestly increased, as per two meta-analyses, although Japanese studies report inconsistent findings, with one showing a slightly decrease and another a slight increase. The risk of malignant lymphoma has increased, whereas the risk of colorectal cancer appears reduced. Additionally, there are concerns regarding the increased risk of lung and skin cancers. However, there is limited evidence specific to patients with RA treated with MTX. According to an Australian report, patients have a higher risk of overall malignancy, with an increased risk of malignant lymphoma, lung cancer, and melanoma. Studies comparing MTX with tumor necrosis factor inhibitors have reported no significant difference in the overall malignancy risk or increased malignancy risk. In White patients, MTX has been associated with an increased risk of recurrence in patients with RA and a history of non-melanoma skin cancer. There is insufficient evidence regarding the risks of MTX use in patients with RA and malignancy. Therefore, decisions regarding MTX use should be made individually based on shared decision-making, and careful follow-up is necessary.